Evaluasi Keselamatan dan Kesehatan Kerja pada Penambangan Batubara PT. Nusa Alam Lestari, Desa Salak, Kecamatan Talawi, Sawahlunto, Sumatera Barat - Rinad Edmon; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Nusa Alam Lestari is an underground coal mining company located in Salak Village, Talawi District, Sawahlunto, West Sumatra. PT. Nusa Alam Lestari has implemented Occupational Safety and Health (HSE) in mining activities, but the application is still not optimal. This is due to the lack of signs and posters of HSE in the work area, not optimal use of personal protective equipment (PPE), some workers who do not comply with company regulations, the occurrence of work accidents, some workers who argue when given directions, the need for existing JSA and SOP television, and the creation of job safety analysis (JSA) and standard operating procedure (SOP) needed. Occupational Safety and Health evaluation that has been applied using questionnaires with knowledge value of 75.74, attitude value of 85.27, and action value of 79.91. Where the overall result of the questionnaire with a score of 80.31. If the value is adjusted based on the likert scale owned at a very good range (80-100). Television and manufacture of JSA and SOP in gas checking activities, jack hammer operation, production activities, lorry operation, and coal hauling to stockpile. Keywords : Underground mining, Jack hammer, Lorry, Job Safety Analysis, Standard Operating Procedure.